2015
DOI: 10.1556/imas.7.2015.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Use of unripe plantain (Musa paradisiaca) in the management of diabetes and hepatic dysfunction in streptozotocin induced diabetes in rats

Abstract: Abstract:Aim: This study aims to investigate the eff ect of unripe plantain (Musa paradisiaca) on markers of hepatic dysfunction in streptozotocin induced diabetic rats. Methods: Blood glucose; relative liver weight (RLW); relative kidney weight (RKW); relative heart weight (RHW); relative pancreatic weight (RPW); serum and hepatic serum aspartate transaminase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP); serum amylase, lipase, total, and conjugated bilirubin; and chemical analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
3
20
1
1
Order By: Relevance
“…The studies occurred in nine different countries: England [41], Sweden [42,43], Bangladesh [44,45,46], Jamaica [47], Venezuela [48], Mexico [49], Brazil [50,51,52,53,54], Nigeria [55], and India [56] (Supplementary file Figure S1) between 1984 and 2019 (Table 1). Almost 40% ( n = 7) of the studies were conducted in Brazil [50,51,52,53,54], probably due to the Brazilian banana production corresponding for about 15% of the worldwide banana production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies occurred in nine different countries: England [41], Sweden [42,43], Bangladesh [44,45,46], Jamaica [47], Venezuela [48], Mexico [49], Brazil [50,51,52,53,54], Nigeria [55], and India [56] (Supplementary file Figure S1) between 1984 and 2019 (Table 1). Almost 40% ( n = 7) of the studies were conducted in Brazil [50,51,52,53,54], probably due to the Brazilian banana production corresponding for about 15% of the worldwide banana production.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the ingredients or foods used in the research, ten studies were conducted with green banana flour [41,43,49,50,51,52,53,55,56,59] and eight with the green banana pulp/biomass [42,44,45,46,47,48,54,60]. Most of the studies used green banana flour, probably due to the highest shelf-life and stability of the product compared to the green banana pulp/biomass [61], and this product is well characterized in the scientific literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of unripe M. paradisiaca in the management of diabetes and hepatic dysfunction in STZ-induced diabetes in rats was assessed by Eleazu and Okafor [30]. The authors reported that intake of unripe extract by diabetic rats resulted in a significant decrease in blood glucose when compared to diabetic control rats; urine glucose and protein decreased with time following treatment with extract of unripe M. paradisiaca.…”
Section: Antidiabetic Activity Of M Paradisiacamentioning
confidence: 99%
“…Evidence suggests that levels of TBARS, a marker of oxidative stress are markedly increased in the liver and pancreas during the progression of diabetes, and that, this plays a major role in pancreatic and hepatocyte damage associated with diabetes [40]. Regeneration of the pancreatic beta cells is one of the proposed mechanisms by which, plant-based drugs are believed to lower blood glucose in STZ-induced diabetic rats because the regenerated beta cells increase the capacity of the endocrine pancreas to synthesize and release insulin, which in turn, promotes cellular glucose utilization [41]. Evaluation of relative vital organs weight showed that EEA-treated diabetic rats had significantly increased liver and pancreatic weights when compared with the diabetic untreated control group.…”
Section: Disscussionmentioning
confidence: 99%